EVALUATION OF MYRICETIN NANOPHYTOSOME WITH THIN-SONICATION LAYER HYDRATION METHOD USING ETHANOL AND ACETONE SOLVENTS - PURNAMASARI, NUR AINI DEWI; DZAKWAN, MUHAMMAD; PRAMUKANTORO, GANET EKO; MAULUDIN, RACHMAT; ELFAHMI (International Journal of Applied Pharmaceutics, 2020)
Objective: Nano-phytosome is a nanotechnology that is used to improve the bioavailability of active ingredients contained in plants by binding to active ingredients with phospholipids which have properties that resemble cell membranes. The active ingredient used in the nano-phytosome formulation is myricetin. Myricetin is a natural flavonoid compound that has antioxidant properties with low bioavailability and permeability. The purpose of this study was to determine the characterization of the nano-phytosome myricetin formulation with different solvents using ethanol and acetone. Methods: Nano-phytosome was made using a thin-sonication hydration method by comparing the acetone and ethanol solvents as well as the variation of the myricetin: phosphatidylcholine: cholesterol ratio. Characterization of nano-phytosome includes particle size, polydisperse index, zeta potential, absorption efficiency and antioxidant activity, and TEM test. Results: Characterization and evaluation of myricetin nano-phytosome using two different solvents, acetone and ethanol. The particle size of all formulas has a size between 10-1000 nm, the use of ethanol solvent produces the smallest particle size of 198.1 ± 1,74 nm and the lowest polydispersity index of 0.175 ± 0,020 in ethanol solvent. Conclusion: The ethanol solvent is better compared to the acetone solvent, and the best formula is formula 4 with the ratio of myricetin: phosphatidylcholine: cholesterol (1: 1: 0.4).